THE EFFECT OF USING SONGS ON STUDENTS’ VOCABULARY AT SMP NEGERI 1 BERASTAGI - Sitepu, Sri Asih; Frida Dian Handini Lubis; Fiscilla Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using songs on students’ vocabulary mastery at SMP Negeri 1 Berastagi. This research applied a quantitative approach with an experimental design, involving two groups: an experimental a class and control class. The sample consisted of eighth-grade students, with 30 students in each class. The instrument used in this study was a vocabulary test in the form of multiple-choice questions. The date were collected through pre-test and post-test. The experimental class was taught by using songs as a learning medium, while the control class was taught using convetional methods without songs. The results of the study showed that the mean score of the experimental class increased from 48 in the pre-test to 82,5 in the post-test. Meanwhile, the control class increased from 52 to 76. The hypothesis testing using the t-test showed that t-count (7,16) was higher than t-table (2,00), wich means that the alternative hypothesis(H1) was accepted and the null hypothesis (H0) was rejected. It can be concluded that the use of songs has a significant effect on students’ vocabulary mastery. Songs can improve students’ vocabulary because they provide repetition, meaningful context, and an enjoyable learning atmosphere, which increases students’ motivation and angagment in learning English.